Borassus flabellifer Effectively Reduces MDA Levels in High Oxidative Stress Population in Jakarta, Indonesia - Reza Aditya Digambiro; Himmi Marsiati; Restu Syamsul Hadi; Edy Parwanto (Talenta Publisher, 2025)
Background: Malondialdehyde (MDA) is commonly used to assess oxidative stress levels. Objective: This study aimed to investigate the effect of Borassus flabellifer fruit consumption on MDA levels in individuals with high oxidative stress, providing insights into the fruit’s potential as a natural antioxidant therapy. Methods: A prospective interventional study was conducted in Jakarta, recruiting fifty participants aged 30–60 years with baseline MDA levels >10 nmol/L. Participants consumed 150 grams of Borassus flabellifer fruit daily for 30 days. Blood samples were collected at baseline and post-intervention to assess MDA levels. Results: The average MDA level decreased significantly from 14.35 ± 2.43 nmol/L to 12.00 ± 1.74 nmol/L after 30 days of fruit consumption (p < 0.0001). The Cohen’s d value of 2.92 indicated a large effect size, demonstrating the intervention’s substantial impact. A strong positive correlation (r = 0.91, p < 0.0001) between baseline MDA levels and reduction was observed, suggesting that participants with higher baseline oxidative stress benefited more from the intervention. Conclusion: Borassus flabellifer fruit consumption effectively reduces MDA levels in individuals with high oxidative stress. The results support the inclusion of this fruit in recommendations for managing oxidative stress-related conditions.